Estimulación temprana y su influencia en el desarrollo del lenguaje en niños/as de 1 a 4 años del centro infantil buen vivir “Pedacitos de Amor”, cantón Milagro, provincia del Guayas - Arteaga Ponce, Carmen Maritza (2016)
Early stimulation helps develop the skills in children it is therefore essential development from the age of one language develops through stimulation, early learning program guidelines conducive to encourage speech development in children. This program develops early stimulation workshops illustrative processes of early stimulation for the development of the child in compliance with the articles of the constitution of the Republic of Ecuador. The proposal put forward was carried out based on the analysis of the collected information and analysis chi square with a question posed asking if early stimulation influences the development of language, social promoters say little and parents than ever concluding that early stimulation influences the development of language in children 1 to 4 years due to lack of knowledge by the parents of the benefits you can get the student to perform therapies are those of language or the development of fine motor skills in children.